Persisting chemosensory impairments in 366 healthcare workers following COVID-19: an 11-month follow-up. (6th May 2022) - Bussiere, Nicholas; Mei, Jie; Levesque-Boissonneault, Cindy; Blais, Mathieu; Carazo, Sara; Gros-Louis, Francois; Laforce, Robert; De Serres, Gaston; Dupre, Nicolas; Frasnelli, Johannes
Abstract: Olfactory and gustatory dysfunctions (OD, GD) are prevalent symptoms following COVID-19 and persist in 6%–44% of individuals post-infection. As only few reports have described their prognosis after 6 months, our main objective was to assess the prevalence of OD and GD 11-month post-COVID-19. We also aimed to determine intraclass correlation coefficients (ICC) of chemosensory self-ratings for the follow-up of chemosensory sensitivity. We designed an observational study and distributed an online questionnaire assessing chemosensory function to healthcare workers with a RT-PCR-confirmed SARS-CoV-2 infection 5- and 11-month post-COVID-19. Specifically, we assessed olfaction, gustation, and trigeminal sensitivity (10-point visual analog scale) and function (4-point Likert scale). We further measured clinically relevant OD using the Chemosensory Perception Test, a psychophysical test designed to provide a reliable remote olfactory evaluation. We included a total of 366 participants (mean [SD] age of 44.8 (11.7) years old). They completed the last online questionnaire 10.6 months (0.7) after the onset of COVID-19 symptoms. Of all participants, 307 (83.9%) and 301 (82.2%) individuals retrospectively reported lower olfactory or gustatory sensitivity during the acute phase of COVID-19. At the time of evaluation, 184 (50.3%) and 163 (44.5%) indicated reduced chemosensory sensitivity, 32.2% reported impairment of olfactory function while 24.9% exhibited clinically relevant OD. Olfactory sensitivity had a high test–retest reliability (ICC: 0.818; 95% CI: 0.760–0.860). This study suggests that chemosensory dysfunctions persist in a third of COVID-19 patients 11 months after COVID-19. OD appears to be a common symptom of post-COVID-19 important to consider when treating patients.